Risk and protective factors for anxiety and obsessive-compulsive disorders: an umbrella review of systematic reviews and meta-analyses. Issue 8 (7th June 2020) - Fullana, Miquel A.; Tortella-Feliu, Miquel; Fernández de la Cruz, Lorena; Chamorro, Jacobo; Pérez-Vigil, Ana; Ioannidis, John P. A.; Solanes, Aleix; Guardiola, Maria; Almodóvar, Carmen; Miranda-Olivos, Romina; Ramella-Cravaro, Valentina; Vilar, Ana; et al.
Abstract: Background: A multitude of risk/protective factors for anxiety and obsessive-compulsive disorders have been proposed. We conducted an umbrella review to summarize the evidence of the associations between risk/protective factors and each of the following disorders: specific phobia, social anxiety disorder, generalized anxiety disorder, panic disorder, and obsessive-compulsive disorder, and to assess the strength of this evidence whilst controlling for several biases. Methods: Publication databases were searched for systematic reviews and meta-analyses examining associations between potential risk/protective factors and each of the disorders investigated. The evidence of the association between each factor and disorder was graded into convincing, highly suggestive, suggestive, weak, or non-significant according to a standardized classification based on: number of cases (>1000), random-effects p -values, 95% prediction intervals, confidence interval of the largest study, heterogeneity between studies, study effects, and excess of significance. Results: Nineteen systematic reviews and meta-analyses were included, corresponding to 216 individual studies covering 427 potential risk/protective factors. Only one factor association (early physical trauma as a risk factor for social anxiety disorder, OR 2.59, 95% CI 2.17–3.1) met all the criteria for convincing evidence. When excluding the requirement for more than 1000 cases, five factor associations met the other criteria for convincing evidence and 22 met the remaining criteria for highly suggestive evidence. Conclusions: Although the amount and quality of the evidence for most risk/protective factors for anxiety and obsessive-compulsive disorders is limited, a number of factors significantly increase the risk for these disorders, may have potential prognostic ability and inform prevention.